2021
DOI: 10.1038/s41467-021-23265-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microbial markers across populations in early detection of colorectal cancer

Abstract: Associations between gut microbiota and colorectal cancer (CRC) have been widely investigated. However, the replicable markers for early-stage adenoma diagnosis across multiple populations remain elusive. Here, we perform an integrated analysis on 1056 public fecal samples, to identify adenoma-associated microbial markers for early detection of CRC. After adjusting for potential confounders, Random Forest classifiers are constructed with 11 markers to discriminate adenoma from control (area under the ROC curve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(130 citation statements)
references
References 55 publications
6
101
0
Order By: Relevance
“…Moreover, changes in the diversity of bacterial communities in the gut is a common event in colorectal tumours. Specific bacteria, such as Fusobacterium nucleatum and several microbial metabolites have been associated with the onset and progression of this disease ( Yachida et al, 2019 ; Castellarin et al, 2012 ; Kostic et al, 2012 ; Wu et al, 2021 ; Feng et al, 2015 ). Using faecal samples from a large cohort of CRC patients in different stages of disease progression Yachida et al (2019) conducted the largest metagenomics ( n = 616) and metabolomics ( n = 406) analysis on human CRC to date ( Yachida et al, 2019 ).…”
Section: Microbial Perturbations In Colorectal Cancer Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, changes in the diversity of bacterial communities in the gut is a common event in colorectal tumours. Specific bacteria, such as Fusobacterium nucleatum and several microbial metabolites have been associated with the onset and progression of this disease ( Yachida et al, 2019 ; Castellarin et al, 2012 ; Kostic et al, 2012 ; Wu et al, 2021 ; Feng et al, 2015 ). Using faecal samples from a large cohort of CRC patients in different stages of disease progression Yachida et al (2019) conducted the largest metagenomics ( n = 616) and metabolomics ( n = 406) analysis on human CRC to date ( Yachida et al, 2019 ).…”
Section: Microbial Perturbations In Colorectal Cancer Developmentmentioning
confidence: 99%
“…The decrease in lactic acid-producing commensals caused by dysbiosis, could lead to progression of early to advanced disease stages ( Feng et al, 2015 ). More recently, bacterial communities were also shown to vary their composition during CRC progression ( Wu et al, 2021 ). By comparing the microbiome in stool samples from 306 adenoma patients, 217 CRC subjects and 252 healthy controls, the authors identified 43 bacteria species with distinguishable differential abundances between controls and patients with adenoma.…”
Section: Microbial Perturbations In Colorectal Cancer Developmentmentioning
confidence: 99%
See 3 more Smart Citations